Herkunft, soziale Identifikation und Studienabbruch Eine empirische Analyse von Passungsproblematiken - Achtelik, Inka (Bildungsforschung | Educational Research, 2023)
Previous research into the causes of academic failure among students both from and not from a migrant background has traditionally focused on empirically and qualitatively measurable problems young people have fitting in between milieu-specific patterns of perception, thought and action and the specific requirements of university as an institution. Against the backdrop of the need for new theoretical and methodological approaches, this study uses self-categorisation theory to empirically and quantitatively investigate how having difficulty fitting in at university due to a lack of social identification with academics is related to the intention of students from and not from a migrant background to drop out of higher education. In addition, the book examines the interplay between social and academic integration more closely.